Taruffo’s Dream - Tuzet, Giovanni (2021)
The paper presents and dialogically discusses Michele Taruffo’s latest book, Verso la decisione giusta (Toward the Right Decision) (2020), focu-sing primarily on the issues of truth, evidentiary reasoning, and the “right decision” as understood by Taruffo. In particular, some differences in the ways of understanding these issues are highlighted and it is suggested that, among the various dimensions of judicial decisions, the rhetorical one cannot be neglected. The paper is divided into sections that roughly correspond to the parts of the book, and develops in the form of a dialo-gue on the basis of a singular dream (“Somnium Taruffi”) whose figures literally quote the passages of the book in question.